Assessing mangrove species diversity, zonation and functional indicators in response to natural, regenerated, and rehabilitated succession. (15th September 2022) - Pimple, Uday; Leadprathom, Kumron; Simonetti, Dario; Sitthi, Asamaporn; Peters, Ronny; Pungkul, Sukan; Pravinvongvuthi, Tamanai; Dessard, Hélène; Berger, Uta; Siri-on, Kraiwut; Kemacheevakul, Patiya; Gond, Valery
Abstract: The United Nations Decade on Ecosystem restoration (2021¬–2030) lists mangrove ecosystems as a restoration priority. Interest in their conservation has increased recently due to their widespread degradation. Anthropogenic stressors and rehabilitation practices, specifically, have resulted in a significant decline in their species compositions. We investigated the knowledge gaps in terms of potential spatial diversity, intertidal zonation, and the historic state of mangrove forest species, and tested the role of environmental factors such as topography, as well as rehabilitation practices on diversity. Diversity and complexity indices, surface elevation, and species and structural diversities along three simplified transect lines over a broad geographical area and under various management practices were analyzed in Trat province, Thailand. Quantitative statistical zonation analyses within each transect and at the landscape-scale were performed using randomization tests and hierarchical cluster analysis. A modified "automatic regrowth monitoring algorithm (ARMA), " based on Landsat (1987–2020) and Sentinel-2 MSI (2015–2020) annual median composites was also used. Fifteen species were identified, with Ceriops tagal as the dominant species. Statistical analysis, however, failed to identify any significant zonation patterns at transect or landscape-scales at specific elevations. Rehabilitated and naturally regenerated stands showed gradual increases in their Normalized Difference Infrared Index over time. After 30 years, the rehabilitated stands made up of Rhizophoraceae monocultures were the same height as the adjacent natural stands. Depending on the location and propagule availability, the diversity and structure of regenerated stands exhibited high variation. Effluent from shrimp farms may have contributed to the disturbance of the forest stands and changes in shrimp farming practices could have facilitated their recovery. The results of the present study provide a valuable diversity baseline for the study site and secondary succession in rehabilitated and regenerated mangroves. The ARMA algorithm has also been confirmed as a valuable tool for future investigations of secondary succession and mangrove biodiversity status. Graphical abstract: Image 1 Highlights: Systematic transect line plots were established. Effects of environmental and anthropogenic settings on mangrove species zonation and diversification were identified. Time series data were utilized to monitor both the historic state and temporal dynamics. A modified automatic regrowth monitoring algorithm (ARMA) was also developed. Trajectories of change dynamics on mangrove ecosystems were also determined.